2018
DOI: 10.1002/ajp.22873
|View full text |Cite
|
Sign up to set email alerts
|

Weak effects of common genetic variation in oxytocin and vasopressin receptor genes on rhesus macaque social behavior

Abstract: The neuropeptides oxytocin (OT) and arginine vasopressin (AVP) influence pair bonding, attachment, and sociality, as well as anxiety and stress responses in humans and other mammals. The effects of these peptides are mediated by genetic variability in their associated receptors, OXTR and the AVPR gene family. However, the role of these genes in regulating social behaviors in non-human primates is not well understood. To address this question, we examined whether genetic variation in the OT receptor gene OXTR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…Our results are consistent with [18], who also investigated rhOXTR markers and social behavior in a similarly-sized sample of rhesus and likewise found no significant effects. We agree with their conclusions that behavioral genetic studies in NHPs likely face the same challenges as in humans: First, samples upwards of tens of thousands would be required to be adequately powered.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with [18], who also investigated rhOXTR markers and social behavior in a similarly-sized sample of rhesus and likewise found no significant effects. We agree with their conclusions that behavioral genetic studies in NHPs likely face the same challenges as in humans: First, samples upwards of tens of thousands would be required to be adequately powered.…”
Section: Discussionsupporting
confidence: 92%
“…Also, studies on captive NHPs provide a more restricted and controlled environment (e.g., controlled diet, less habitat variation), which might lead to stronger genetic effects. A recent study on the effects of variants in OXTR and AVP receptor genes (AVPR1A, AVPR1B) on behavior in rhesus macaques, however, failed to replicate previous results and showed only very small effects of the 12 SNPs that were examined (Madlon-Kay et al 2018). Alongside the emerging consistency of findings that single genetic variants have only small effects on complex traits, Madlon-Kay and colleagues (2018) discuss other methodological difficulties, including missing control of genetic relatedness within the population and/or missing adjustment of pvalues, that raise doubt about earlier positive results.…”
Section: Gene-environment Interplaymentioning
confidence: 75%
“…Links between vasopressin and other aspects of social behavior, on the other hand, have been demonstrated in both apes and monkeys. In rhesus macaques, variation in sociability is associated with measures of vasopressin in cerebral spinal fluid, despite no significant associations between AVPR1A alleles and social behaviors, such as grooming, passive contact, approaches and aggression . In chimpanzees, several studies have shown that polymorphisms in AVPR1A are associated with individual variation in different dimensions of personality, including social “smarts” (using coalitions and engaging in reciprocal grooming and play) and sociability .…”
Section: Introductionmentioning
confidence: 99%